Signal peptide exchange alters HIV-1 envelope antigenicity and immunogenicity - Upadhyay, Chitra; Rao, Priyanka; Behzadi, Mohammad Amin; Feyznezhad, Roya; Lambert, Gregory S.; Kumar, Rajnish; Kumar, Madhu; Yang, Weiming; Jiang, Xunqing; Luo, Christina C.; Nadas, Arthur; Arthos, James; et al. (Frontiers in Immunology, 2024)
HIV-1 envelope (Env) is the key target for antibodies (Abs) against the virus and thus an important HIV-1 vaccine component. Env is synthesized from a gp160 precursor with a signal peptide (SP) at its N-terminus. This study investigated how the SP influenced Env antigenicity and immunogenicity. Env from two HIV-1 isolates, AA05 and AC02, were analyzed as gp120 and gp160 in their native wild-type (WT) forms and as chimeras where the SPs were swapped between the two isolates to generate AA05-02 and AC02-05. The recombinant AC02 gp120 protein was antigenically superior to AA05 as indicated by higher reactivity with most monoclonal Abs (mAbs) tested. When SPs were swapped, the antigenicity of chimeric gp120s (AA05-02 and AC02-05) resembled that of gp120s from which the SPs were derived; AA05-02 was similar to AC02 and vice versa. The same trend was observed with the reactivity of glycan probes: AA05-02 and AC02 showed similar affinity to high-mannose specific mAb and lectins. Interestingly, the antigenicity of gp160s showed an opposite pattern; membrane-bound gp160 expressed with AA05 SP (AA05 and AC02-05) showed greater mAb binding than gp160 with AC02 SP (AC02 and AA05-02). The immunogenicity testing was subsequently performed in mice using three vaccine types: gp120 protein, gp120 DNA+gp120 protein, and gp120 DNA+gp160 DNA. With the gp120 protein, AA05-02 induced stronger cross-reactive binding Ab responses than AA05 WT, and AC02 elicited stronger cross-reactive responses than AC02-05, indicating that the AC02 SP enhanced gp120 immunogenicity. However, when DNA vaccines were included, as in gp120 DNA+gp120 protein, and gp120 DNA+gp160 DNA, the use of heterologous SP diminished the immunogenicity of the WT immunogens. Moreover, of the three vaccine regimens tested, only gp120 DNA+gp160 DNA immunization elicited low level Tier 2 neutralizing Abs, with AA05 WT inducing Abs with greater neutralization capabilities than AA05-02. Hence, while SP swapping is a common practice in constructing Env immunogens, data from this study highlight the importance of careful consideration of the effects of replacing native SPs on the immunogenicity of Env vaccines.